Hepatocellular Carcinoma Screening With Computed Tomography Using the Arterial Enhancement Fraction With Radiologic-Pathologic Correlation. Issue 1 (January 2016) - Huber, Adrian Thomas; Schuster, Frederik; Ebner, Lukas; Bütikofer, Yanik; Ott, Daniel; Leidolt, Lars; Jöres, Andreas; Montani, Matteo; Heverhagen, Johannes; Christe, Andreas
Abstract : Objective: The aim of this study was to investigate the performance of the arterial enhancement fraction (AEF) in multiphasic computed tomography (CT) acquisitions to detect hepatocellular carcinoma (HCC) in liver transplant recipients in correlation with the pathologic analysis of the corresponding liver explants. Materials and Methods: Fifty-five transplant recipients were analyzed: 35 patients with 108 histologically proven HCC lesions and 20 patients with end-stage liver disease without HCC. Six radiologists looked at the triphasic CT acquisitions with the AEF maps in a first readout. For the second readout without the AEF maps, 3 radiologists analyzed triphasic CT acquisitions (group 1), whereas the other 3 readers had 4 contrast acquisitions available (group 2). A jackknife free-response reader receiver operating characteristic analysis was used to compare the readout performance of the readers. Receiver operating characteristic analysis was used to determine the optimal cutoff value of the AEF. Results: The figure of merit ( θ = 0.6935) for the conventional triphasic readout was significantly inferior compared with the triphasic readout with additional use of the AEF ( θ = 0.7478, P < 0.0001) in group 1. There was no significant difference between the fourphasic conventional readout ( θ = 0.7569) and the triphasic readout ( θ = 0.7615, P = 0.7541) with the AEF in group 2. Without the AEF, HCC lesions were detected with a sensitivity of 30.7% (95% confidence interval [CI], 25.5%–36.4%) and a specificity of 97.1% (96.0%–98.0%) by group 1 looking at 3 CT acquisition phases and with a sensitivity of 42.1% (36.2%–48.1%) and a specificity of 97.5% (96.4%–98.3%) in group 2 looking at 4 CT acquisition phases. Using the AEF maps, both groups looking at the same 3 acquisition phases, the sensitivity was 47.7% (95% CI, 41.9%–53.5%) with a specificity of 97.4% (96.4%–98.3%) in group 1 and 49.8% (95% CI, 43.9%–55.8%)/97.6% (96.6%–98.4%) in group 2. The optimal cutoff for the AEF was 50%. Conclusion: The AEF is a helpful tool to screen for HCC with CT. The use of the AEF maps may significantly improve HCC detection, which allows omitting the fourth CT acquisition phase and thus making a 25% reduction of radiation dose possible.